CFD analysis of the effect of heterogeneous hull roughness on ship resistance. (15th August 2022) - Ravenna, Roberto; Song, Soonseok; Shi, Weichao; Sant, Tonio; De Marco Muscat-Fenech, Claire; Tezdogan, Tahsin; Demirel, Yigit Kemal
Abstract: Hull roughness significantly increases ship resistance, power, and fuel consumption. Although it is typically spatially heterogeneous, little research has dealt with heterogeneously distributed roughness on ship hulls. Therefore, this study investigates the heterogeneous hull roughness effect on ship resistance using Computational Fluid Dynamics (CFD). A series of CFD simulations were conducted on the KRISO Container Ship (KSC) hull model to accurately predict the effect of heterogeneous hull roughness on ship resistance. Specifically, the StarCCM + software package was adopted to develop Unsteady Reynolds Averaged Navier–Stokes (URANS)-based CFD simulations with a modified wall-function approach. Various surface coverage conditions were modelled, including homogeneous (i.e., smooth and full rough conditions) and heterogeneous conditions (i.e., different smooth/rough wetted surface ratios). Eventually, the present findings showed that increased roughness on the bulbous bow region has the most significant impact on ship resistance. Moreover, the introduction of a so-called roughness impact factor correlated the added resistance of the heterogeneous roughness scenarios to the corresponding rough wetted surface area. Accordingly, the rough bulbous bow scenario presented a higher roughness impact factor than the other rough hull cases. Highlights: Towing tests of KRISO Container Ship (KCS) model were simulated using Computational Fluid Dynamics (CFD). The effect of hull roughness on the hydrodynamics of the KCS hull was assessed. Spatially heterogeneous hull roughness with different smooth/rough surface ratios was investigated. Roughness Impact Factors (RIF) were defined to correlate hull roughness conditions with predicted resistance coefficients.